(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article theoretically analyzes the main psychological problems of career orientation of students in modern schools. The results of a number of researches related to the important tasks of professional education, stages of professional formation, career choice, career orientation, understanding and definition of professional identity are described.